Implementing Social Media Management Against Sustainability Business on the Micro, Small and Medium Enterprises - Ramli, Yanto; Erna Sofriana Imaningsih; Dudi Permana; Mochamad Soelton; Aldina Shiratina (PT FORMOSA CENDEKIA GLOBAL, 2024)
The goal of a sustainable business strategy is to create long-term value for the firm, its stakeholders, and society at large by integrating economic, environmental, and social objectives into corporate goals, actions, and planning. It has long been believed that developing value outside of these parameters is illegitimate. Among the emerging nations that continues to protect micro, small, and medium-sized businesses is Indonesia. MSMEs, or micro, small, and medium-sized enterprises, are the foundation of the economy. The government has worked very hard to maintain and grow MSMEs in the community. MSMEs are divided into a number of sectors by the regional administration, including trade, home industry, agriculture, food, fisheries, handicrafts, and other industries. Today's MSMEs face several obstacles, including disorganized data and a dearth of industrial facilities capable of producing commodities with significant added value. The government's financial and aid initiatives are frequently off course due to irregularities and disorganized data. Additionally, the government is currently concentrating on enhancements to facilitate better organization of MSMEs data. One significant initiative that will be carried out in the nation is the strengthening and transformation of the digital ecosystem. The secret to accelerating recovery and boosting the competitiveness of the national economy, particularly raising MSMEs' productivity and performance, is to digitize rural areas faster than cities